Reversible Regulation of Enzyme Activity by pH-Responsive Encapsulation in DNA Nanocages - Kim, Seong Ho; Kim, Kyoung-Ran; Ahn, Dae-Ro; Lee, Ji Eun; Yang, Eun Gyeong; Kim, So Yeon (AMER CHEMICAL SOC, 2017)
Reversible regulation of enzyme activity by chemical and physical stimuli is often achieved by incorporating stimuli-responsive domains in the enzyme of interest. However, this method is suitable for a limited number of enzymes with well-defined structural and conformational changes. In this study, we present a method to encapsulate enzymes in a DNA cage that could transform its conformation depending on the pH, allowing reversible control of the accessibility of the enzyme to the surrounding environment. This enabled us to regulate various properties of the enzyme, such as its resistance to protease-dependent degradation, binding affinity to the corresponding antibody, and most importantly, enzyme activity. Considering that the size and pH responsiveness of the DNA cage can be easily adjusted by the DNA length and sequence, our method provides a broad impact platform for controlling enzyme functions without modifying the enzyme of interest.
Keywords: MOLECULE PULL-DOWN; 3-DIMENSIONAL STRUCTURE; PROTEIN INTERACTIONS; OPTOGENETIC CONTROL; RIBONUCLEASE-A; DRUG-DELIVERY; RELEASE; NANOSTRUCTURES; TRANSCRIPTION; PATHWAYS